2017
DOI: 10.1155/2017/4768505
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Brazed Zinc-Coated Structured Sheet Metal

Abstract: Arc brazing has, in comparison to arc welding, the advantage of less heat input while joining galvanized sheet metals. The evaporation of zinc is reduced in the areas adjacent to the joint and improved corrosion protection is achieved. In the automotive industry, lightweight design is a key technology against the background of the weight and environment protection. Structured sheet metals have higher stiffness compared to typical automobile sheet metals and therefore they can play an important role in lightwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The color of the product of corrosion was found to be reddish for T1 and whitish for T3. It is known that the white product of corrosion in galvanized steel can be mainly composed of zinc based products of corrosion such as zinc hydroxide, zinc carbonate and zinc oxide in chloride containing aqueous environments [19]. Therefore, from the observed color of the rusts, it could be understood that the amount of Zinc rich product of corrosion is increased as the coating thickness is increased.…”
Section: Resultsmentioning
confidence: 99%
“…The color of the product of corrosion was found to be reddish for T1 and whitish for T3. It is known that the white product of corrosion in galvanized steel can be mainly composed of zinc based products of corrosion such as zinc hydroxide, zinc carbonate and zinc oxide in chloride containing aqueous environments [19]. Therefore, from the observed color of the rusts, it could be understood that the amount of Zinc rich product of corrosion is increased as the coating thickness is increased.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that in non-load carrying joints such softening might result in the joint area being the weakest component of a structure [1]. GMAB (or MIG brazing) is a well-known process in industries where thin-walled structures are constructed using galvanized steel plates [2][3][4][5]. By using GMAB instead of conventional fusion welding, the beneficial effect of the galvanized layer, e.g.…”
Section: Introductionmentioning
confidence: 99%